2011
DOI: 10.1002/jssc.201000843
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive two‐dimensional liquid chromatography with evaporative light‐scattering detection for the analysis of triacylglycerols in Borago officinalis

Abstract: An optimized 2-D liquid chromatography (LC×LC) set-up, based on the different selectivities of a silver ion (Ag) and a non-aqueous reversed phase (NARP), employed in the first (D1) and the second dimension (D2), respectively, in combination with evaporative light-scattering detection (ELSD), has been developed for the analysis of the triacylglycerol (TAG) fraction in a Borago officinalis oil. The 2-D set-up, thanks to the complementary separation selectivity provided by the two columns, allowed to distribute 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…An increase in the percentage of entrances into the open arms and time spent in open arms, lacking a changed locomotors activity are confirmed as a potent sign for an anxiolytic compounds effect (23). Borage is of great interest among medical and nutritional research groups due to its high content of some useful compounds (10,11,39). Linolenic acid and palmitic acid are collected from flowers and high levels of α-Linolenic acid is in mature leaves (40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in the percentage of entrances into the open arms and time spent in open arms, lacking a changed locomotors activity are confirmed as a potent sign for an anxiolytic compounds effect (23). Borage is of great interest among medical and nutritional research groups due to its high content of some useful compounds (10,11,39). Linolenic acid and palmitic acid are collected from flowers and high levels of α-Linolenic acid is in mature leaves (40).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its folkloric use as an antispasmodic remedy and based on the traditional use of Borago officinalis in asthma, Borago officinalis extract was tested for its possible spasmolytic and bronchodilator effects (17). Borago officinalis seed oil is used in pharmaceutical products, especially for its high content in α-linolenic acid, an essential and unusual fatty acid (10,43). It has been shown that palmitic, linoleic and stearic acids were dominant in the seed oil of borage (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique performance of these particle columns, offering the advantages of higher efficiencies and rugged design, capable of high-pressure operation, was demonstrated in some studies Marchetti et al, 2007;Cavazzini et al, 2007;Cunliffe and Maloney, 2007;Donato et al, 2009). Because of these attributes, these columns were chosen as 2 D of LC Â LC systems, and several research groups (Mondello, Dugo, Jandera and Cifuentes) used them in natural products applications (Hajek et al, 2008;Dugo et al, 2008cDugo et al, , 2009aRusso et al, 2011;Mondello et al, 2011;Cacciola et al, 2012;Leme et al, 2014;Jandera, 2012;Cesla et al, 2009;Hájek and Jandera, 2012;Montero et al 2013aMontero et al ,b, 2014Montero et al , 2016aDonato et al, 2016). In two of the abovementioned references (Dugo et al, 2008c;Hajek et al, 2008) the performance of a partially porous short column was compared with that of a monolithic column.…”
Section: Advances In Practicementioning
confidence: 99%
“…The former may arise from inadequate peak focusing on the top of the 2 D column for a matter of solvent compatibility. In fact, the 1 D mobile phase, serving as the fraction solvent (hexane), possesses a higher eluent strength compared with the 2 D mobile phase, possibly compromising the whole LC × LC separation [26][27][28][29]. In this work, thanks to the transfer of 36 fraction volumes as low as 20 μl from 1 D to 2 D, it was possible to solve this issue, making the transfer of incompatible solvents possible without peak shape deterioration or resolution losses.…”
Section: Bstop-flow^ag + -Lc × Narp-lc Analyses Of the Triacylglyceromentioning
confidence: 99%